bahasa indonesia bahasa indonesia: bahasa indonesia - Jessen Kho (Politeknik Kutaraja, 2021)
The decline in Gross Domestic Product (GDP) and the recession in Indonesia due to the pandemic succeeded in attracting the author's attention to thoroughly analyze the causes and solutions for the decline in GDP. After going through the observation process, the authors managed to find and conclude that the decline in GDP and this recession was preceded by a decrease in corporate and public income due to policies established by the government to contain the spread of the virus. This decrease in income has a domino effect for all sectors of the economy. Therefore, the Indonesian government and Bank Indonesia implemented an expansionary fiscal and monetary policy in an effort to restore a recessionary economy and increase Indonesia's GDP.